2017
DOI: 10.3389/fmars.2017.00169
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Short-Term Functioning of a Benthic Community from a Deep Norwegian Fjord Following Deposition of Mine Tailings and Sediments

Abstract: The extraction of minerals from land-based mines necessitates the disposal of large amounts of mine tailings. Dumping and storage of tailings into the marine environment, such as fjords, is currently being performed without knowing the potential ecological consequences. This study investigated the effect of short-term exposure to different deposition depths of inert iron ore tailings (0.1, 0.5, and 3 cm) and dead subsurface sediment (0.5 and 3 cm) on a deep water (200 m) fjord benthic assemblage in a microcosm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 93 publications
(127 reference statements)
1
16
0
Order By: Relevance
“…While the exclusion of metazoan meiofauna could have altered our results somewhat, this likely had less effect on our results than the exclusion of the Foraminfera. Previous investigations have shown metazoan meiofauna do not respond as strongly to phytodetritus C input as macrofauna or Foraminifera (Gooday et al ; Moodley et al , ; Nomaki et al ; Guilini et al ; Pozzato et al ; Mevenkamp et al ; Stratmann et al ). Among the Foraminifera, monothalmids dominate assemblages in the eastern CCFZ, including the UK1 and OMS areas (Nozawa et al ; Goineau and Gooday ).…”
Section: Discussionmentioning
confidence: 97%
“…While the exclusion of metazoan meiofauna could have altered our results somewhat, this likely had less effect on our results than the exclusion of the Foraminfera. Previous investigations have shown metazoan meiofauna do not respond as strongly to phytodetritus C input as macrofauna or Foraminifera (Gooday et al ; Moodley et al , ; Nomaki et al ; Guilini et al ; Pozzato et al ; Mevenkamp et al ; Stratmann et al ). Among the Foraminifera, monothalmids dominate assemblages in the eastern CCFZ, including the UK1 and OMS areas (Nozawa et al ; Goineau and Gooday ).…”
Section: Discussionmentioning
confidence: 97%
“…In general, recovery of mobile fauna occurred faster than that of sessile fauna and small organisms tend to recover faster than large organisms (Gollner et al, 2017;Jones et al, 2017). These deep-sea experiments clearly indicated that substrate deposition led to changes in meiofauna community composition and vertical distribution (Kaneko et al, 1997;Miljutin et al, 2011) which has also been observed in experiments on meiobenthic communities from shallower depths (Maurer et al, 1986;Mevenkamp et al, 2017;Schratzberger et al, 2000). However, it remains unclear which thickness of sediment deposition evoked the meiofaunal response in the deep sea and if it is possible to reproduce the results under more controlled conditions on a short term.…”
Section: Introductionmentioning
confidence: 54%
“…Changes in vertical nematode distributions have also been reported in a shallow-water study investigating the impacts of the disposal of experimental dredging material (Schratzberger et al, 2000) and a short-term laboratory experiment testing the effect of instantaneous burial with inert tailings and dead, native sediment (Mevenkamp et al, 2017). These studies found that the amount and frequency of sediment burial are interactive factors showing that frequent but low amounts cause less severe changes than high amounts and instantaneous burial (Schratzberger et al, 2000); but also that substrate burial may cause nematode mortality of up to 50 % in the added substrate layer, which was measured by using a staining technique (Mevenkamp et al, 2017). Moreover, Mevenkamp et al (2017) indicated that burial with 0.1 cm of tailings may already reduce the functioning of bathyal, benthic fjord ecosystems in terms of fresh organic carbon remineralization.…”
Section: Crushed Nodule Substrate Burial Induces Changes In Meiobenthmentioning
confidence: 75%
“…These factors include the location of the outfall pipe, the volume disposed and the physical, chemical and hydrodynamic conditions of the targeted area, together with the degree of tolerance/sensitivity of the organisms in the local site and adjacent areas that may be affected by increased water turbidity and concentrations of metals or metalloids due to tailing plumes (Mineral Policy Institute, 1999;McKinnon, 2002). Most of the known effects of tailings on marine environments that are described in the literature have been based on tailings disposal in littoral, nearshore shallow waters and coastal fjords (e.g., Kathman et al, 1983;Burd, 2002;Lee and Correa, 2005;Kvassnes and Iversen, 2013;Mevenkamp et al, 2017). Studies published in the open literature specific to the impacts of DSTD are fewer (e.g., Hughes et al, 2015), and those in the gray literature are often not readily accessible (e.g., Shimmield et al, 2010;LIPI, 2014;Simpson and Angel, 2015).…”
Section: Dstd Impacts and Ecosystem Recovery Potentialmentioning
confidence: 99%
“…Thus, the order of species arrival, and the rate at which the faunal community will regenerate after tailings disposal has ceased will be site-specific, and also species-specific (Hughes et al, 2015). However, even higher-taxon level identification is sufficient to detect large-scale tailings impact in shallow water environments (Lee and Correa, 2005) and deep-sea sediments (Montagna et al, 2013;Hughes et al, 2015;Mevenkamp et al, 2017).…”
Section: Dstd Impacts and Ecosystem Recovery Potentialmentioning
confidence: 99%